Development of Punjabi-English (PunEng) Parallel Corpus for Machine Translation System - Deep, Kamal; Kumar, Ajit; Goyal, Vishal (International Journal of Engineering and Technology, 2018)
This paper describes the creation process and statistics of Punjabi English (PunEng) parallel corpus. Parallel corpus is the main requirement to develop statistical machine translation as well as neural machine translation. Until now, we do not have any availability of PunEng parallel corpus. In this paper, we have shown difficulties and intensive labor to develop parallel corpus. Methods used for collecting data and the results are discussed, errors during the process of collecting data and how to handle these errors will be described.